Jesus the Samaritan - Penwell, Stewart (BRILL, 2017)
In Jesus the Samaritan: Ethnic Labeling in the Gospel of John , Stewart Penwell examines how ethnic labels function in the Gospel of John. After a review of the discourse history between
10.1163/9789004390706
Keywords: Hochschulschrift; Ethnizität; Samaritaner